2023
DOI: 10.1097/wno.0000000000001900
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis After COVID-19 Vaccination: An Analysis of the Vaccine Adverse Event Reporting System

Abstract: Background: To investigate the association of optic neuritis (ON) after the COVID-19 vaccines. Methods: Cases of ON from Vaccine Adverse Event Reporting System (VAERS) were collected and divided into the prepandemic, COVID-19 pandemic, and COVID-19 vaccine periods. Reporting rates were calculated based on estimates of vaccines administered. Proportion tests and Pearson χ2 test were used to determine significant differences in reporting rates of ON after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Several individual case reports of optic neuritis following COVID-19 vaccination have been published in the literature, with optic neuritis being considered the most commonly reported neuro-ophthalmic event following COVID-19 vaccination. [25][26][27][28] Jaffrey et al calculated the reporting rates of optic neuritis, collecting cases from the Vaccine Adverse Event Reporting System, and divided them into the pre-pandemic, COVID-19 pandemic and COVID-19 vaccine periods. 28 The authors showed no significant increase in the reporting rate of optic neuritis following COVID-19 vaccination when compared with the range of incidence in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several individual case reports of optic neuritis following COVID-19 vaccination have been published in the literature, with optic neuritis being considered the most commonly reported neuro-ophthalmic event following COVID-19 vaccination. [25][26][27][28] Jaffrey et al calculated the reporting rates of optic neuritis, collecting cases from the Vaccine Adverse Event Reporting System, and divided them into the pre-pandemic, COVID-19 pandemic and COVID-19 vaccine periods. 28 The authors showed no significant increase in the reporting rate of optic neuritis following COVID-19 vaccination when compared with the range of incidence in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Jaffrey et al calculated the reporting rates of optic neuritis, collecting cases from the Vaccine Adverse Event Reporting System, and divided them into the pre-pandemic, COVID-19 pandemic and COVID-19 vaccine periods. 28 The authors showed no significant increase in the reporting rate of optic neuritis following COVID-19 vaccination when compared with the range of incidence in the general population. 28 Similarly, our study did not detect an increase in the reporting rate of optic neuritis when compared with the cases expected from the UK incidence data.…”
Section: Discussionmentioning
confidence: 99%
“…Jaffry et al 1 noted that limitations of this study include those inherent to any passive surveillance system. Jaffry et al 1 mentioned that controlled studies are needed to establish a clear causal relationship. ON after the COVID-19 vaccines.…”
mentioning
confidence: 97%
“…We would like to share ideas on the publication “Optic Neuritis (ON) After COVID-19 Vaccination: An Analysis of the Vaccine Adverse Event Reporting System. 1 ” Jaffry et al 1 investigated the association of some cases of ON may be temporally associated with the COVID-19 vaccines; however, there is no significant increase in the reporting rate compared with the incidence. Jaffry et al 1 noted that limitations of this study include those inherent to any passive surveillance system.…”
mentioning
confidence: 99%
See 1 more Smart Citation